The association between benzodiazepine prescription and aberrant drug-related behaviors in primary care patients receiving opioids for chronic pain. Issue 4 (1st October 2016) - Park, Tae Woo; Saitz, Richard; Nelson, Kerrie P.; Xuan, Ziming; Liebschutz, Jane M.; Lasser, Karen E.
ABSTRACT: Background: Benzodiazepine use has been associated with addiction-related risks, but little is known about its association with aberrant drug-related behaviors in patients receiving opioids for chronic pain. The authors examined the association between receipt of a benzodiazepine prescription and 2 aberrant drug-related behaviors, early opioid refills and illicit drug (cocaine) use in patients receiving opioids for noncancer chronic pain. Methods: This was a retrospective cohort study of 847 patients with ≥1 visit to either a hospital-based primary care clinic or one of two community health centers between September 1, 2011, and August 31, 2012. All patients received ≥3 opioid prescriptions written at least 21 days apart within 6 months, and ≥1 urine drug screen during the study period. A Cox proportional hazards model estimated the hazard of a second early opioid refill, defined as an opioid prescription written 7–25 days after the previous prescription for the same drug, as a function of time-varying benzodiazepine prescription. A logistic regression model examined the relationship between benzodiazepine prescription and a positive urine test for cocaine. Models were adjusted for demographics and mental/substance use disorder diagnoses. Results: Twenty-three percent ( n = 196) of patients received ≥1 benzodiazepine prescription during the study period. Twenty-two percent ( n = 183) of patients had ≥2 early opioid refills, and 11% ( n = 93) had ≥1 positive urine drug tests for cocaine. Receipt of benzodiazepine prescription was associated with an increased hazard of having a second early opioid refill, adjusted hazard ratio = 1.54 (95% confidence interval [CI]: 1.09–2.18), but not associated with a positive cocaine test, adjusted odds ratio = 1.07 (95% CI: 0.55–2.23). Conclusions: Among primary care patients receiving chronic opioid therapy, benzodiazepine prescription was associated with early opioid refills but not with cocaine use. Further research should better elucidate the risks and benefits of prescribing benzodiazepines to patients receiving opioids for chronic pain.